Profiles of successful and less successful learners of English pronunciation in Croatian primary schools - Josipović Smojver, Višnja (Array, 2013)
The present paper is a case study based on the observation of four groups of focal primary-school learners (altogether 26 subjects) during a period of four years ( fifth to eighth grade, i.e., ages eleven to fourteen). Half of the subjects were from a city and half were from a small town. Every year each of the pupils was recorded in an interview which consisted of two parts: a task ful filment in English and a motivational interview in their mother tongue, Croatian. In this way a total of 97 interviews (about 20 hours of recorded speech) was obtained. Three independent qualified assessors analysed auditorily their pronunciation features, focusing on the presence or absence of `core' ELF features, as defi ned by Jenkins (2002). Thus they looked primarily at features of pronunciation like substitutions in the phonemic inventory ; the preservation of the vocalic length contrasts ; aspiration in consonants ; the overall degree of fluency and intelligibility. On the basis of this evaluation, four best pronouncers and four least successful pronouncers were singled out. Next we looked for correlations of good pronunciation in this sense with the type and degree of the subjects' motivation for learning English and using it for international communication, their awareness of the status of English as a global language, and their day-to-day exposure to international (i.e. not necessarily native) English outside school. Finally, conclusions were reached about the implications of the results for learning and teaching English in the function of preparing learners for successful communication on a global scale.